1999
DOI: 10.1177/00027649921954390
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Labor in Asian Immigrant Families

Abstract: This article explores the effects of employment patterns on gender relations among contemporary Asian immigrants. The existing data on Asian immigrant salaried professionals, self-employed entrepreneurs, and wage laborers suggest that economic constraints and opportunities have reconfigured gender relations within contemporary Asian America society. The patriarchal authority of Asian immigrant men, particularly those of the working class, has been challenged due to the social and economic losses that they suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 18 publications
3
61
1
Order By: Relevance
“…It was expected that the distinct dress of many women in this predominantly Muslim sample might contribute to differential levels of stress across gender. Earlier work with Asian (Espiritu 1999;Huhr and Kim 1990;Kiefer et al 1985) and Arab samples (Amer and Hovey 2007) also suggested some increased stress for females as they may shift roles or add additional workload upon immigration. In this case, however, while females had higher reported depression, females and males did not differ significantly on any of the measures of acculturative stress.…”
Section: Relationship Of Demographic Variables To Acculturative Stresmentioning
confidence: 98%
See 1 more Smart Citation
“…It was expected that the distinct dress of many women in this predominantly Muslim sample might contribute to differential levels of stress across gender. Earlier work with Asian (Espiritu 1999;Huhr and Kim 1990;Kiefer et al 1985) and Arab samples (Amer and Hovey 2007) also suggested some increased stress for females as they may shift roles or add additional workload upon immigration. In this case, however, while females had higher reported depression, females and males did not differ significantly on any of the measures of acculturative stress.…”
Section: Relationship Of Demographic Variables To Acculturative Stresmentioning
confidence: 98%
“…The influence of gender on the acculturation process and related stressors is complex and varies in part due to variation in gender roles ideology across cultures. Females have been reported by a number of researchers (e. g. Hurh and Kim 1990;Kiefer et al 1985) to have greater difficulty in adapting to the new culture, with either fewer opportunities to acculturate when remaining in the home, or stressed by demands of employment coupled with a traditional division of labor, resulting in a heavy workload overall (Espiritu 1999) Amer and Hovey (2007) note that Arab American women may be uniquely "at-risk" for mental health and physical problems as they are impacted by pressure to deal with Western cultural behaviors and influences on their children while at the same time experiencing their own social discomfort. Among Muslim immigrants, women appear to be readily targeted in terms of discriminatory acts (Hassouneh and Kulwicki 2007) and may be somewhat more identifiable as a target than Muslim men due to distinctions in dress, such as the wearing of a hijab.…”
Section: Variables Potentially Related To Acculturative Stress and Itmentioning
confidence: 99%
“…It is probable that younger participants (64% are below the age of 35) who have lower educational levels may experience higher economic hardships, as they have fewer resources with which to overcome their hardships. Previous studies have also indicated that immigrants with higher socio-economic status generally tend to report better health, and those with lower socio-economic status are at risk for poorer psychological health (e.g., Espiritu, 1999;Shen & Takeuchi, 2001).…”
Section: Demographic Factors and Adaptationmentioning
confidence: 99%
“…Equally important, how is gender implicated in household strategies and the construction of flexibility? As feminist scholars have demonstrated, migration is a gendered process with uneven, often contradictory, and frequently different implications for women and men living in the same households (Espiritu 2003;Itzigsohn and GiorguliSaucedo 2005;Mahler and Pessar 2006;Menjivar 2003;Pessar 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hardill 2002), shifting in its composition over time and space as members pursue closely intertwined economic and social strategies. Further, in unpacking the relations of power at the household level, scholars show the deep connections between gender identities and the structuring of men's and women's employment, and the ability to negotiate uncertain labour market conditions (Espiritu 2003;Menjivar 2003). As Buzar et al (2005, p.…”
Section: Introductionmentioning
confidence: 99%